Domestic Harmony and Da’wah Values in Mu’asyarah Bil Ma’ruf: An Exegetical Study of Wahbah Zuhaili’s Tafsir al-Munir - Fazlurrahman, Lalu Muhamad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study is motivated by the phenomenon of domestic quarrels, both in real life and in cyberspace, which often stem from the failure of households to implement the principle of mu’asyarah bil ma’ruf in marital life. Such neglect frequently results in disputes between spouses. The purpose of this research is to explain the implementation of mu’asyarah bil ma’ruf in domestic life according to Wahbah Zuhaili and to analyze its impact on family harmony. Specifically, this paper addresses two main questions: how the concept of mu’asyarah bil ma’ruf is formulated in Wahbah Zuhaili’s Tafsir al-Munir and how its application influences the quality of marital relationships. This research employs a library research design with documentation as the primary method of data collection. The main source is Wahbah Zuhaili’s Tafsir al-Munir, analyzed using a qualitative approach by interpreting textual data and relating it to relevant references for deeper understanding. The findings reveal that mu’asyarah bil ma’ruf is a fundamental obligation of the husband toward his wife, serving as the cornerstone for establishing a family based on sakinah, mawaddah, and rahmah. Without proper fulfillment of rights and obligations, it is impossible for couples to achieve a harmonious and loving household. This research contributes to the field of da’wah and family studies by emphasizing the importance of cultivating a peaceful, compassionate, and morally grounded family environment as the essential foundation for individual and social development.